Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Study on separation and dynamic characteristics of ilmenite and chlorite regulated by structural parameters of spiral chute - Shuling Gao; Bochao Li; Chunyu Liu; Qian Wang; Xiaohong Zhou; Guixia Fan; Daoguang Teng (Minerals Engineering, 2026)

Phase evolution mechanism of selenium during hydrothermal conversion–atmospheric sulfuric acid leaching of copper anode slimes - Fang Shuling; Rao Shuai; Ma Zhiyuan; Liu Yejian; Tian Lei; Chen Lijie; Liu Zhiqiang; Zhang Liheng (Hydrometallurgy, 2026)

Selective recovery of vanadium, molybdenum, and nickel from full-particle spent hydrodesulfurization catalysts via microwave roasting-ammonia leaching - Haoyu Xu; Liang Yu; Zhiyuan Ma; Shuling Fang; Shuai Rao; Dongxing Wang; Lijuan Duan; Hongyang Cao; Zhiqiang Liu (Journal of Environmental Chemical Engineering, 2026)

Coupling of spectroscopy and nitrogen-oxygen isotopes unveils the mechanisms of dissolved organic matter and nitrate pollution in lakes within the agro-pastoral transition zone - Guodong Chai; Fang Yang; Haiqing Liao; Debin Jia; Weiying Feng; Chiamin Ho; Dongpin Liu; Shuling Chen; Jianguo Liu; Huibin Yu (Journal of Environmental Sciences, 2026)

Designing sustained-release sodium carriers: Oil-modified starch gels enhance the texture and delay sodium release in low-sodium shrimp protein gels - Menghan Wang; Yang Li; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Ultrasonically treated pea starch modulates oil absorption in corn starch-based deep-fried products: Insights into gel network architecture, interfacial behavior, and molecular dynamics simulations - Menghan Wang; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Multifunctional drug-loaded cement for microenvironment remodeling to promote osteoporotic bone regeneration in Kümmell's disease - Dongping Wang; Yihan Gao; Shuling Gu; Ziqi Feng; Zhizhao Li; Guanxiong Wang; Chang Liu; Yihao Zhu; Yang Shao; Qingtao Li; Yongxian Li; Xiaodong Cao; et al. (Chemical Engineering Journal, 2026)

White Spot Syndrome Virus Envelope Protein VP 53 B Functions as a Trypsin Inhibitor and Interacts With Hemocyanin - Wenxu Xia; Lingqi Zhuang; Yuchen Liu; Kai Li; Bing Qin; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Fish Diseases, 2026)
White spot syndrome virus (WSSV) remains a persistent and significant threat to the global shrimp aquaculture industry. However, its pathogenic mechanisms remain incompletely understood, and no effective intervention strategies are currently available. In this study, we investigated the functional role of VP53B, an envelope structural protein of WSSV, using a combination of infection bioassays, protein structure prediction, protease inhibition assays and protein binding analyses. Our results demonstrate that VP53B is a critical determinant of per os (oral) infection in shrimp, including Procambarus clarkii (crayfish) and Litopenaeus vannamei (whiteleg shrimp). Functionally, VP53B acts as a trypsin inhibitor and interacts with host hemocyanin. We propose that through modulation of shrimp trypsin and hemocyanin, VP53B disrupts the prophenoloxidase‐activating system, a key innate immune pathway, thereby facilitating successful WSSV infection. This study provides new insights into the molecular mechanisms underlying WSSV oral infectivity and highlights VP53B as a potential target for therapeutic intervention.

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Optimal scheduling for CCHP in highway service areas considering equipment status switching and variable coefficient of performance - Lingzhi Zhang; Xi Kang; Shuling Liu; Ruifeng Shi; Zhuangzhuang Liu; Limin Jia (Sustainable Cities and Society, 2026)

Transcriptomic and metabolomic analysis reveals melatonin treatment in delaying postharvest yellowing in broccoli through ABA-pigment metabolism network - Yue Wang; Jianhui Cheng; Wenbo Lei; Shuling Shen; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Recent advances in the formation, characterization, and applications of starch-polyphenol complexes: A review - Bo Han; Qianhan Ma; Shuling Yan; Shiyin Jia; Yao Hu; Hao Xu; Siyuan Liu; Hao Zhang; Pengjie Wang; Jiayue Guo (Food Chemistry, 2026)

DBD synergistic UiO-66/GO-n: A new dawn for efficient defluorination and rapid degradation of fluorine-containing organic pollutants - Yejian Liu; Lijuan Duan; Shuling Fang; Wuming Xie; Qingnan Zeng; Jingyi Huang; Hongyang Cao; Zhiyuan Ma (Process Safety and Environmental Protection, 2026)

Engineering hydrodynamics via pitch-diameter ratio to intensify eco-efficient separation of fine hematite/quartz in spiral chute - Shuling Gao; Qian Wang; Xiaohong Zhou; Chunyu Liu; Bochao Li (Minerals Engineering, 2026)

Hydrothermal depolymerization of PET microplastics assisted by pyroelectric-induced polarization in BTO/TiO₂ composite - Shuling Shen; Ziwei Feng; Huixin Feng; Zijian Zhang; Tongxin Huang; Zhihong Tang; Xinjuan Liu; Jing Li; Huixin Xiu (Journal of Environmental Chemical Engineering, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Chronic Fluoride Exposure from Brick Tea Consumption Disrupts Bone Remodeling and Contributes to Bone Loss in Chinese Population with Skeletal Fluorosis - Hongjiang Long; Yubo Liu; Pinggui Lei; Ting Hu; Zhijuan Shao; Yu Luo; Shuling Zhang; Jinshu Li; Peng Luo; Zhenting Zhang; Shaofeng Wei (Biological Trace Element Research, 2026)

Synergistic curdlan gum/xanthan gum system improves shrimp myofibrillar protein gel properties via enhanced network structure, texture and water holding capacity - Shuling Zhou; Xuening Yu; Menghan Wang; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

N-doped CoFe alloy coupled to hierarchical carbon as 3D catalysts for synergistic reversible oxygen electrocatalysis in Zn-air batteries - Ze Li; Tianfeng Ma; Zhen Feng; Haiyan Wang; Shuling Liu; Yanyan Liu; Hucheng Zhang; Jianji Wang; Baojun Li (Chemical Engineering Journal, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Mechanisms of blue light-mediated inhibition of chlorophyll degradation in ‘Newhall’ sweet orange during postharvest - Hui Sun; Yuwei Zhou; Sijia Liu; Qianqian Yu; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2026)

Mechanisms of water-rock interaction and its impact on swelling and crack behavior of argillaceous dolomite in tunnel uplift zones - Zihang Liu; Kang Huang; Shuling Huang; Xianfeng Liu; Fei Yu; Shanxiong Chen; Zhangjun Dai (Bulletin of Engineering Geology and the Environment, 2026)

Boosting methanogenesis in high-solids anaerobic digestion of corn straw by coupling hydrogen nanobubbles with biochar - Chuanfei Bian; Yiming Shi; Mao Du; Shuaishuai Ma; Shiyu Li; Hao Liu; Luyao Wei; Shuling Cao; Binshou Wang; Hongliang Wang; Wanbin Zhu (Journal of Environmental Chemical Engineering, 2025)

Cation doping and defects engineering induced NiCoFeP@NC composite as anode for high-performance sodium-ion batteries - Qiangqiang Shi; Shuling Liu; Zhipeng Qin; Xinyue Liu; Xiangxiang Wang; Rui Su; Jianbo Tong (Chemical Engineering Journal, 2025)

Effect of the downward bevel angle on the particle radial migration behaviour and secondary flow in spiral separators - Meng Lingguo; Gao Shuling; Liu Tianlin; Kuang Jingzhong; Yu Mingming (Minerals Engineering, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Corrigendum to “Dynamic surface restructuring of MoP@Mo-MOF electrocatalysts for efficient alkaline water splitting” [Chem. Eng. J. 521 (2025) 166885] - Xinjuan Liu; Jun Xu; Kun Yang; Dalal A. Alshammari; Mohamed H. Helal; Hang Zhang; Shuai Zhang; Chenchen Zhang; Shuling Shen; Zhihong Tang; Yuhua Xue; Zeinhom M. El-Bahy; et al. (Chemical Engineering Journal, 2025)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Phosphorylated Scrophularia ningpoensis polysaccharides mitigate oxidative stress and modulate immunity by regulating the gut microbiota in cyclophosphamide-treated mice - Lufen Huang; Jianan Wang; Litao Wang; Shuling Liu; Xinru Niu; Zhouwen Wu; Kexin Guo; Si Gong; Bowen Wei; Zhaochun Wang; Jianing Mi; Yufeng Liu; et al. (Food Bioscience, 2025)

Dynamic surface restructuring of MoP@Mo-MOF electrocatalysts for efficient alkaline water splitting - Xinjuan Liu; Jun Xu; Kun Yang; Dalal A. Alshammari; Mohamed H. Helal; Hang Zhang; Shuai Zhang; Chenchen Zhang; Shuling Shen; Zhihong Tang; Yuhua Xue; Zeinhom M. El-Bahy; et al. (Chemical Engineering Journal, 2025)

Study on the deformation and failure mechanism of tertiary water-rich soft rock tunnels based on the moisture migration-fracture coupling model - Kang Huang; Shuling Huang; Xiuli Ding; Yuting Zhang; Dengxue Liu; Zhangjun Dai (Tunnelling and Underground Space Technology, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Molecular interactions and physiological effects of oyster-derived synthetic peptide-calcium complex: Insight in improving the bone growth and health - Xuening Yu; Guang Li; Shijie Dou; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2025)

Integration of machine learning and meta-analysis reveals the behaviors and mechanisms of antibiotic adsorption on microplastics - Shuangshuang Bi; Ruoying Wu; Xiang Liu; Peng Wei; Shuling Zhao; Xinru Ma; Enfeng Liu; Hongfeng Chen; Jinling Xu (Journal of Hazardous Materials, 2025)

Dose-dependent developmental fluoride exposure leads to neurotoxicity and impairs excitatory synapse development - Wenjin Qiu; Xiaoyu Wang; Shuling Zhang; Zhenting Zhang; Kaiju Zhang; Zhijuan Shao; Yubo Liu; Ruting Wei; Liangzhao Chu; Peng Luo (Archives of Toxicology, 2025)

Corrigendum to “Piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water” [Chem. Eng. J. 484 (2024) 149514] - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2025)

Discovery, engineering, and applications of the ketoreductases from Metabacillus lacus in the synthesis of chiral (Hetero)aryl alcohols - Shuling Zhang; Yuqing Zhang; Weixi Kong; Wanting Guo; Quan Yuan; Yanjun Jiang; Yunting Liu (Chemical Engineering Journal, 2025)

Simultaneous electrodeposition of vanadium oxide and polyaniline derivatives and its application in aqueous zinc ion storage - Xiaojuan Lai; Yihao Li; Jiafei Niu; Jiatuo Li; Yuhang Cao; Shuling Liu; Chao Wang (Chemical Engineering Journal, 2025)

Impacts of shale gas wastewater leaks on neighboring crops: Physiological and morphological responses of tomatoes - Fengming Li; Xulin Yu; Yushun Yang; Wei Tao; Mengting Zhu; Di Zhang; Shuling Shi; Huiqiang Li; Peng Tang; Alberto Tiraferri; Baicang Liu (Process Safety and Environmental Protection, 2025)

Ni2P/Cu3P bimetallic phosphide embedded in nitrogen-doped carbon as SIB anode: Constructed hetero interface promoting fast Na+ diffusion and storage performance - Shuling Liu; Qiangqiang Shi; Xinyue Liu; Jiaru Fan; Lei Ren; Jianbo Tong (Chemical Engineering Journal, 2024)

Enhancement mechanism of metal ions on the flotation behavior of muscovite in sodium oleate system - Wenbao Liu; Tao Zheng; Yonglun Wang; Wengang Liu; Yanbai Shen; Shuling Gao; Qiang Zhao (Minerals Engineering, 2024)

Biochar enhances Cd mineralization through microbially induced carbonate precipitation as a soil remediation strategy for rice paddies - Dinghua Peng; Xianghan Chen; Shuling Zhang; Guoquan Zeng; Chaoqun Yan; Huanyan Luo; Huakang Liu; Heng Xu (Chemosphere, 2024)

Effective and mechanistic insights into shale gas wastewater reverse osmosis concentrate treatment using ozonation-biological activated carbon process - Mengting Zhu; Peng Tang; Xulin Yu; Fengming Li; Shuling Shi; Di Zhang; Jialin Shi; Wei Tao; Xia Ruan; Lujian Liu; Baicang Liu (Science of The Total Environment, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

The application of multi-point FBG bolt in measuring the excavation damaged zone of underground caverns - Gang Han; Shuling Huang; Xiuli Ding; Yuting Zhang; Jun He; Pengcheng Liu; Peiyang Yu; Dengxue Liu (Tunnelling and Underground Space Technology, 2024)

A review of the advances and prospects of aqueous Dual-Ion batteries - Shuhua Guan; Qiaoling Peng; Xiuli Guo; Ye Zheng; Enda Liao; Shuling Sun; Kyungsoo Shin; Botian Liu; Xiaolong Zhou; Caineng Zou; Yongbing Tang (Chemical Engineering Journal, 2024)

Microplastic pollution promotes soil respiration: A global‐scale meta‐analysis - Shuling Zhao; Matthias C. Rillig; Haijian Bing; Qingliang Cui; Tianyi Qiu; Yongxing Cui; Josep Penuelas; Baiyan Liu; Shiqi Bian; Fazel Abdolahpur Monikh; Jing Chen; Linchuan Fang (Global Change Biology, 2024)
Microplastic (MP) pollution likely affects global soil carbon (C) dynamics, yet it remains uncertain how and to what extent MP influences soil respiration. Here, we report on a global meta‐analysis to determine the effects of MP pollution on the soil microbiome and CO 2 emission. We found that MP pollution significantly increased the contents of soil organic C (SOC) (21%) and dissolved organic C (DOC) (12%), the activity of fluorescein diacetate hydrolase (FDAse) (10%), and microbial biomass (17%), but led to a decrease in microbial diversity (3%). In particular, increases in soil C components and microbial biomass further promote CO 2 emission (25%) from soil, but with a much higher effect of MPs on these emissions than on soil C components and microbial biomass. The effect could be attributed to the opposite effects of MPs on microbial biomass vs. diversity, as soil MP accumulation recruited some functionally important bacteria and provided additional C substrates for specific heterotrophic microorganisms, while inhibiting the growth of autotrophic taxa (e.g., Chloroflexi , Cyanobacteria ). This study reveals that MP pollution can increase soil CO 2 emission by causing shifts in the soil microbiome. These results underscore the potential importance of plastic pollution for terrestrial C fluxes, and thus climate feedbacks.

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

Transcriptomic analysis reveals the role of abscisic acid and ethylene in regulating starch-source biosynthesis associated with soft nose disorder in ‘Keitt’ mango fruit during postharvest - Yuan Cheng; Ying Wang; Lichuan Lou; Yuxuan Wang; Binger Dai; Yue Wang; Mariama Kebbeh; Chen Huan; Shuling Shen; Yan Liu; Xiaolin Zheng; Jeffrey K. Brecht (Postharvest Biology and Technology, 2024)

Efficient piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2024)

An efficient three-dimensional (3D) inversion algorithm for recovering magnetic targets when remanence exists - Yuan Fang; Shuling Li; Guofeng Liu; Xiaohong Meng; Jun Wang; Shijing Zheng (Acta Geophysica, 2024)

Systematic metabolic engineering of Yarrowia lipolytica for the enhanced production of erythritol - Shuling Yang; Xuewei Pan; Jiajia You; Baomin Guo; Zuyi Liu; Ying Cao; Guomin Li; Minglong Shao; Xian Zhang; Zhiming Rao (Bioresource Technology, 2024)

Insights into boosting catalytic hydrogen evolution over Co doping Ru nanoparticles - Hao Wen; Ruofan Shen; Yanyan Liu; Xiaoyan Huang; Shuling Liu; Zhikun Peng; Xianli Wu; Xianji Guo; Erjun Liang; Huiyu Yuan; Baojun Li; Jianchun Jiang (Fuel, 2023)

In-depth insight into correlations between gut microbiota and dietary fiber elucidates a dietary causal relationship with host health - Lili Li; Shuling Yan; Shuangjiang Liu; Ping Wang; Wenjun Li; Yuetao Yi; Song Qin (Food Research International, 2023)

Establishment of a prognostic model for melanoma based on necroptosis-related genes - Xiaohui Sui; Xiaodan Zhang; Junde Zhao; Jinxing Liu; Shuling Li; Xiaowen Zhang; Juntao Wang (Functional & Integrative Genomics, 2023)

Bacterial diversity of middle ear cholesteatoma by 16S rRNA gene sequencing in China - Qiulin Liang; Ruiqing Long; Shuling Li; Chaowu Jiang; Jingyu Gao; Sheng Cheng; Zhuohui Liu; Biao Ruan (Functional & Integrative Genomics, 2023)
In this study, the bacterial diversity of acquired middle ear cholesteatoma (MEC) was evaluated to reveal its pathogenesis and provides a guide for the use of antibiotics. Twenty-nine cases of acquired MEC and eight cases of healthy middle ears undergoing cochlear implantation (CI) were evaluated. Full-length 16S rRNA gene sequencing was performed to profile the bacterial communities in lesions and healthy tissues of the middle ear. ACE ( P = 0.043) and Chao1 ( P = 0.039) indices showed significant differences in alpha diversity ( P < 0.05). Analysis of PERMANOVA/Anosim using the Bray–Curtis distance matrix results suggested that the between-group differences were greater than the within-group differences ( R = 0.238, P < 0.05, R 2 = 0.066, P < 0.05). Bacterial community analysis revealed that Alphaproteobacteria at the class level and Caulobacterales and Sphingomonadales at the order level were significantly different ( P < 0.05). In the LefSe (Linear discriminant analysis effect size) analysis, Porphyromonas bennonis was elevated, and Bryum argenteum and unclassified Cyanobacteriales were reduced at the species level in MEC ( P < 0.05). Fifteen metabolic pathways were found to be significantly different between the two groups by analysing the abundance of metabolic pathways in level 2 of the Kyoto Encyclopaedia of Genes and Genomes (KEGG). Seven and eight metabolic pathways were significantly elevated in the MEC and control groups, respectively ( P < 0.05). The role of bacteria in the pathogenesis of acquired MEC was further refined through analysis of metabolic pathways. These findings indicate that the acquired MEC and healthy middle ear contain more diverse microbial communities than previously thought.

Mechanistic insights into the detoxification of Cr(VI) and immobilization of Cr and C during the biotransformation of ferrihydrite-polygalacturonic acid-Cr coprecipitates - Hanyue Zhang; Yang Lu; Zhuozhi Ouyang; Wenjing Zhou; Xinyue Shen; Kun Gao; Shuling Chen; Yang Yang; Shiwen Hu; Chongxuan Liu (Journal of Hazardous Materials, 2023)

Capture of copper cyanide complex ions based on self-assembly of ionic liquids actuation and application to cyanide wastewater - Weichao Li; Wengang Liu; Wenbao Liu; Shijie Zhou; Shuling Gao; Yanbai Shen (Hydrometallurgy, 2023)

Temperature effects on microbial dissolved organic matter metabolisms: Linking size fractions, fluorescent compositions, and functional groups - Gang Tang; Binrui Li; Bowei Zhang; Shiwen Hu; Shuling Chen; Tong Liu; Qianqian Wang; Han Qiao; Xing Zheng (Science of The Total Environment, 2023)

Slope position mediates the co-utilization of phosphorus by plants and microbes through rhizosphere processes in a phosphorus-limited forest - Tianyi Qiu; Jialuo Yu; Liyuan He; Ji Liu; Qingliang Cui; Yongxing Cui; Chengjiao Duan; Shuling Zhao; Yunqiang Wang; Linchuan Fang (CATENA, 2023)

Synergistic interplay between Azospirillum brasilense and exogenous signaling molecule H2S promotes Cd stress resistance and growth in pak choi (Brassica chinensis L.) - Qingliang Cui; Dongdong Liu; Hansong Chen; Tianyi Qiu; Shuling Zhao; Chengjiao Duan; Yongxing Cui; Xiaozhen Zhu; Herong Chao; Yuhan Wang; Jie Wang; Linchuan Fang (Journal of Hazardous Materials, 2023)

The double-edged effect of single atom metals on photocatalysis - Xiaoming Liu; Fengting He; Yangming Lu; Shuling Wang; Chaocheng Zhao; Shuaijun Wang; Xiaoguang Duan; Huayang Zhang; Xiaoli Zhao; Hongqi Sun; Jinqiang Zhang; Shaobin Wang (Chemical Engineering Journal, 2023)

Transcriptome analysis reveals the mechanisms of hepatic injury caused by long-term environmental exposure to atrazine in juvenile common carp (Cyprinus carpio L.) - Jingbo Liu; Guangcheng Yang; Yanxia Gao; Xinran Li; Yuting Long; Shuling Wei; Yuxin Zhao; Shanshan Sun; Shujuan Gao (Environmental Science and Pollution Research, 2022)

Research on carbon emission measurement and low-carbon path of regional industry - Xue Wu; Shuling Zhou; Guowei Xu; Conghu liu; Yingyan Zhang (Environmental Science and Pollution Research, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Low-carbon technology service mode with revenue-sharing contract considering advance funding risk - Huiying Mao; Yuxia Guo; Yingyan Zhang; Shuling Zhou; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven evaluation and optimization of the sustainable development of the logistics industry: case study of the Yangtze River Delta in China - Heping Ding; Yujia Liu; Yingyan Zhang; Shuxia Wang; Yuxia Guo; Shuling Zhou; Conghu Liu (Environmental Science and Pollution Research, 2022)

Viscoelastic-plastic constitutive model with non-constant parameters for brittle rock under high stress conditions - Shuling Huang; Chuanqing Zhang; Xiuli Ding; Liu Yang (European Journal of Environmental and Civil Engineering, 2022)

Correction to: Data-driven analysis and evaluation of regional agriculture for high quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven analysis and evaluation of regional agriculture for high-quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Permeability Anisotropy in High Dip Angle Coal Seam: A Case Study of Southern Junggar Basin - Taiyuan Zhang; Shu Tao; Dazhen Tang; Shuling Tang; Hao Xu; Aobo Zhang; Yifan Pu; Yingying Liu; Qiang Yang (Natural Resources Research, 2021)

Regulation of biomass, pigments, and lipid production by Chlorella vulgaris 31 through controlling trophic modes and carbon sources - Weibao Kong; Shuling Yang; Hui Wang; Huanran Huo; Baomin Guo; Na Liu; Aimei Zhang; Shiquan Niu (Journal of Applied Phycology, 2020)

Optimized back analysis method for stress determination based on identification of local stress measurements and its application - Qitao Pei; Xiuli Ding; Yuankun Liu; Bo Lu; Shuling Huang; Jing Fu (Bulletin of Engineering Geology and the Environment, 2019)

Characterization and prevalence of a novel white spot syndrome viral genotype in naturally infected wild crayfish, Procambarus clarkii, in Shanghai, China - Luzhi Jiang; Jinzhou Xiao; Liyuan Liu; Yingjie Pan; Shuling Yan; Yongjie Wang (VirusDisease, 2017)

Physiological responses of three soybean species (Glycine soja, G. gracilis, and G. max cv. Melrose) to salinity stress - Haoran Liu; Jinhui Song; Lijun Dong; Di Wang; Shuling Zhang; Jianfeng Liu (Journal of Plant Research, 2017)

Prevalence and genomic analysis of infectious hypodermal and hematopoietic necrosis virus (IHHNV) in Litopenaeus vannamei shrimp farmed in Shanghai, China - Chao Chai; Yuchen Liu; Xiaoming Xia; Hongming Wang; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2016)

Differential Immune Responses and Protective Effects in Avirulent Mycobacterial Strains Vaccinated BALB/c Mice - Laicheng Liu; Ruiling Fu; Xuefeng Yuan; Chunwei Shi; Shuling Wang; Xianyu Lu; Zhao Ma; Xiaoming Zhang; Weiyan Qin; Xionglin Fan (Current Microbiology, 2015)

Construction of an Off-On Fluorescence System Based on Carbon Dots for Trace Pyrophosphate Sensing - Qiaoli Yue; Yining Hou; Shuzhen Yue; Kaimin Du; Tongfei Shen; Lei Wang; Shuling Xu; Haibo Li; Jifeng Liu (Journal of Fluorescence, 2015)

Evaluation of two-year Jewish genetic disease screening program in Atlanta: insight into community genetic screening approaches - Yunru Shao; Shuling Liu; Karen Grinzaid (Journal of Community Genetics, 2015)

The Ac124 protein is not essential for the propagation of Autographa californica multiple nucleopolyhedrovirus, but it is a viral pathogenicity factor - Changyong Liang; Dandan Lan; Shuling Zhao; Lulu Liu; Yanan Xue; Yongli Zhang; Yun Wang; Xinwen Chen (Archives of Virology, 2015)

Quantitative structure–activity relationship studies of diarylpyrimidine derivatives as anti-HIV drugs using new three-dimensional structure descriptors - Jianbo Tong; Li Zhong; Xiang Zhao; Shuling Liu; Ping Wang (Medicinal Chemistry Research, 2014)

QSAR studies of antituberculosis drug using three-dimensional structure descriptors - Jianbo Tong; Yang Chen; Shuling Liu; Xiameng Xu (Medicinal Chemistry Research, 2013)

Expression of glr gene encoding glutamate racemase in Bacillus licheniformis WX-02 and its regulatory effects on synthesis of poly-γ-glutamic acid - Feng Jiang; Gaofu Qi; Zhixia Ji; Shuling Zhang; Jun Liu; Xin Ma; Shouwen Chen (Biotechnology Letters, 2011)

Human embryonic germ cells isolation from early stages of post-implantation embryos - ShanRong Liu; HouQi Liu; YuQiong Pan; ShuPing Tang; Jun Xiong; Ning Hui; ShuLing Wang; ZhongTian Qi; LingSong Li (Cell and Tissue Research, 2004)